Blast Loading Effect on RCC Components by Simulation in Software (International Journal of Engineering Management Science, 2021)
Blast loads action on structures are very critical due to increasing threats from accidental and industrial accidental explosions. This study investigates the behavior of reinforced concrete structures subjected to blast loading using simulation in Ansys software. Finite element modelling is performed to assess deformation, stress distribution, and failure mechanisms. The results highlight the importance of structural design considerations for blast resistance of structures and accordingly measures. Blast loads are high intensity, short duration loads. This paper presents investigation of blast loading on RC structures using simulation. Procedure to apply load, preprocessing, processing and postprocessing, result, graph etc.The primary objective of this study is to investigate the structural response under blast loading using explicit dynamic analysis in ANSYSExplicit Dynamics.
Keywords: Blast Load; Overpressure; Shock Wave; Impulse; Structural Response; Ansys; Dynamic Analysis; Reinforced Cement Concrete; Standoff Distance; Ambient Temperature; Explosive Temperature